Past performance evaluation in repeated procurement: A simple model of handicapping - Gian Luigi Albano; Berardino Cesi (Fondazione Eni Enrico Mattei (FEEM), 2008)
When procurement contracts are awarded through competitive tendering participating firms commit ex ante to fulfil a set of contractual duties. However, selected contractors may find profitable to renege ex post on their promises by opportunistically delivering lower quality standards. In order to deter ex post moral hazard, buyers may use different strategies depending on the extent to which quality dimensions are contractible, that is, verifiable by contracting parties and by courts. We consider a stylized repeated procurement framework in which a buyer awards a contract over time to two firms with different efficiency levels. If the contractor does not deliver the agreed level of performance the buyer may handicap the same firm in future competitive tendering. We prove that under complete information extremely severe handicapping is never a credible strategy for the buyer, rather the latter finds it optimal to punish the opportunistic firm so as to make the pool of competitors more alike. In other words, when opportunistic behaviour arises, the buyer should use handicapping to "level the playing field".
Keywords: C73; D82; D44; H57; K12; L14; 330; Repeated Procurement; Handicapping; Relational Contracts; Stick and Carrot Strategy; Beschaffung; Auktion; Nichtpreiswettbewerb; Vertrag; Wiederholte Spiele